Gambaran Kadar Asam Urat pada Wanita Usia Menopause di Desa Rancapanggung Kecamatan Cililin - Marsya Mutmainah; Agus Sudrajat (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
gout attacks women who are generally women at the age of menopause. During menopause, women experience a decrease in the function of the ovaries, resulting in a decrease in the function of the hormone estrogen, so that during menopause, women are susceptible to an increase in uric acid levels in the blood. To find out the description of uric acid levels in menopausal women in the Rancapanggung Village area, Cililin District, West Bandung Regency. The research method used was descriptive observational, the sample consisted of 32 menopausal women in the Rancapanggung Village area, Cililin District, West Bandung Regency. The data collection technique uses a frequency distribution table with direct uric acid examination of menopausal women. The results of the study showed the frequency distribution of uric acid levels in menopausal women, most of the respondents had high uric acid levels because previously most of the respondents had a history of gout. Most respondents had high uric acid levels in the age range 50 years and above.The high levels of uric acid in menopausal women in the Rancapanggung Village area, Cililin District, West Bandung Regency are mostly in the age range 50 years and above.